Key Features of a Language for Special Purposes - Sadirova Dinara Sadikovna; Berdiyorova Mehriniso Xolmamatovna (Genius Journals, 2023)
This article addresses the problem of the main characteristics of a language for special purposes, in connection with which the possibility of separating the concepts of a language for special purposes (Language for Special Purposes - LSP) is considered, various approaches to its definition are analyzed, the scope of LSP is clarified, a parallel is drawn between LSP and ESP ( English for Special Purposes).
Keywords: Special; language; linguistics; academic